Greening the Academy Ecopedagogy Through the Liberal Arts - Fassbinder, Samuel Day.; II, Anthony J. Nocella; Kahn, Richard; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
This is the academic Age of the Neoliberal Arts. Campuses$1 (Bas places characterized by democratic debate and controversy, wide ranges of opinion typical of vibrant public spheres, and service to the larger society$1 (Bare everywhere being creatively destroyed in order to accord with market and military models befitting the academic-industrial complex. While it has become increasingly clear that facilitating the sustainability movement is the great 21st century educational challenge at hand, this book asserts that it is both a dangerous and criminal development today that sustainability in higher education has come to be defined by the complex-friendly (3z(Bgreen campus(3y (Binitiatives of science, technology, engineering and management programs. By contrast, Greening the Academy: Ecopedagogy Through the Liberal Arts takes the standpoints of those working for environmental and ecological justice in order to critique the unsustainable disciplinary limitations within the humanities and social sciences, as well as provide tactical reconstructive openings toward an empowered liberal arts for sustainability. Greening the Academy thus hopes to speak back with a collective demand that sustainability education be defined as a critical and moral vocation comprised of the diverse types of humanistic study that will benefit the well-being of our emerging planetary community and its numerous common locales.s
Keywords: Education; Education; Education (general).